2022
DOI: 10.1186/s12913-022-07667-2
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the quality of cardiac rehabilitation programs by measuring adherence to the Australian quality indicators

Abstract: Background Every year, over 65,000 Australians experience an acute coronary syndrome (ACS) and around one-third occur in people with prior coronary heart disease. Cardiac rehabilitation (CR) aims to prevent a repeat ACS by supporting patients’ return to an active and fulfilling lifestyle. CR programs are efficacious, but audits of clinical practice show variability of program delivery, which may compromise patient outcomes. Core components, quality indicators and accreditation of programs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
5
1
1
Order By: Relevance
“…Interestingly however, the collection of quality-of-life data had a non-significant increase from the pre-COVID timepoint to time of survey completion for both program commencement and completion data collection ( Supplementary Table 3 ). This is in opposition to another recent South Australian study, which demonstrated that the health-related quality-of-life quality indicator was the least-measured indicator [ 20 ]. It is possible that CR clinicians in our national sample were more aware of quality of life and thus the value of collecting this data.…”
Section: Discussioncontrasting
confidence: 82%
“…Interestingly however, the collection of quality-of-life data had a non-significant increase from the pre-COVID timepoint to time of survey completion for both program commencement and completion data collection ( Supplementary Table 3 ). This is in opposition to another recent South Australian study, which demonstrated that the health-related quality-of-life quality indicator was the least-measured indicator [ 20 ]. It is possible that CR clinicians in our national sample were more aware of quality of life and thus the value of collecting this data.…”
Section: Discussioncontrasting
confidence: 82%
“…had coronary heart disease or chronic heart failure (NYHA I, II, and III). This is consistent with cardiac rehabilitation eligibility criteria reported by Australian programs [ 27 ].…”
Section: Methodssupporting
confidence: 89%
“…Our model’s control group aimed to reflect current Australian practice for centre-based cardiac rehabilitation. We used a recently conducted study to determine the length and number of sessions per week in Australian practice [ 27 ]. The study reported that patients had, on average, ten cardiac rehabilitation sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified two errors in the author names. Firstly, the two co-authors’ names J Hendriks and C Gallagher were mistakenly merged into one name ‘Hendriks Gallagher JC’.…”
mentioning
confidence: 99%